Audit Quality Perspectives in Indonesia - Andri, Muhammad; Putra, Rheza Chandra; Saputra, Kanta Rio; Gunawan, Sania Yolanda (Universitas Pendidikan Indonesia, 2020)
In the past 5 years, there have been at least 5 major cases involving prominent public accounting firms in Indonesia and seizing public attention. This motivates the author to look back at the concept of audit quality that is understood in Indonesia. The author realizes that there has been no research on the concept of audit quality conducted by referring to scientific publications that have been published in trusted journals. The main objective of this study is to discover the concept of audit quality that has been generally understood in Indonesia and the factors that influence it. The study was conducted using a descriptive method with a qualitative approach so it could provide a broader understanding and also be able to assist other researchers to conduct research related to audit quality with a more comprehensive understanding. This study reviews a total 47 empirical studies and academic publications in Indonesia ranging from year 2015 to year 2019. Data sources in the form of academic publications were obtained from the Digital Referral Gate website (GARUDA), a portal that contains Indonesian academic references and is under the auspices of the Ministry of Research, Technology and Higher Education (Kemenristekdikti). Based on the analysis, the review reveals that (1) the majority of researchers in Indonesia consider audit quality from an input-outcomes perspective developed from the definition of audit quality according to DeAngelo (1981), (2) the use of a variety of audit quality indicators used in research in Indonesia shows that audit quality is hard to measure objectively, (3) the factors that influence audit quality that are most frequently studied are internal factors, and (4) the majority of research related to audit quality is conducted using a quantitative approach. However, quantitative approach is unable to capture the actual audit practices which is necessary to understand audit quality. (5) cases that occur in Indonesia and the results of this study indicate that audit quality must be seen as a whole construction, from input, process, output and context. Audit quality cannot be obtained only with competent human resources, but must be accompanied by an audit process that is in accordance with standards, results of audits that are comprehensive and in context.